1998
DOI: 10.1001/archinte.158.21.2389
|View full text |Cite
|
Sign up to set email alerts
|

Attitude and Self-reported Practice Regarding Prognostication in a National Sample of Internists

Abstract: Background: Since prognostication appears increasingly important in clinical practice, especially in end-oflife care, we examined physicians' experiences and attitudes regarding it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
303
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(321 citation statements)
references
References 36 publications
14
303
0
4
Order By: Relevance
“…We found just one participant in our study who had previously discussed prognosis with their doctor, consistent with the contention that clinicians share prognosis less often than their patients would prefer. 29,[36][37][38] Participant perspectives in our study also supported those who have argued for clinician-initiated discussions of prognosis that are highly personalized, 17 empathic, 30 and begin with the explicit determination of each patient's preferences for discussion. 29 As evidence of the deeply personal nature of patient preferences for prognostic information, we noted that many patients viewed prognosis as uncertain, yet some saw this as a reason to avoid prognostic information, while others preferred that clinicians simply acknowledge uncertainty in their prognostic discussions (final quotes, Tables 2 and 3).…”
Section: Resultssupporting
confidence: 76%
“…We found just one participant in our study who had previously discussed prognosis with their doctor, consistent with the contention that clinicians share prognosis less often than their patients would prefer. 29,[36][37][38] Participant perspectives in our study also supported those who have argued for clinician-initiated discussions of prognosis that are highly personalized, 17 empathic, 30 and begin with the explicit determination of each patient's preferences for discussion. 29 As evidence of the deeply personal nature of patient preferences for prognostic information, we noted that many patients viewed prognosis as uncertain, yet some saw this as a reason to avoid prognostic information, while others preferred that clinicians simply acknowledge uncertainty in their prognostic discussions (final quotes, Tables 2 and 3).…”
Section: Resultssupporting
confidence: 76%
“…26 However, these results are more in line with reports of providers working in specialized settings such as the intensive care unit (ICU), where predictions may be more accurate. 27,28 It is noteworthy, though, that the hospice nurses in this study were subject to the same optimism bias that has been described elsewhere for physicians 24,25 and that they consistently underestimated 7-day mortality.…”
Section: Discussionsupporting
confidence: 55%
“…This is unexpected because previous studies have found that health care providers are poor at predicting prognosis, 24,25 and even palliative care providers tend to be optimistic. 26 However, these results are more in line with reports of providers working in specialized settings such as the intensive care unit (ICU), where predictions may be more accurate.…”
Section: Discussionmentioning
confidence: 87%
“…16,17 In doing so, we touched on a subject that even many physicians prefer not to address due to concerns about causing parents distress. [18][19][20][21] We therefore evaluated parents' experiences as study participants.…”
Section: Introductionmentioning
confidence: 99%